2015
DOI: 10.1111/1556-4029.12855
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soft Tissue on Temperature Estimation from Burnt Bone Using Fourier Transform Infrared Spectroscopy

Abstract: This study investigated the effect of soft tissue and different exposure times on the prediction of burning temperatures of bone when using Fourier transform infrared spectroscopy (FTIR). Ovis aries rib bones were burnt at different temperatures and for varying time intervals. Results of a linear regression analysis indicated that burn temperatures can be predicted with a standard error of ±70 °C from defleshed bone spectra. Exposure time does not have a significant impact on prediction accuracy. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…The modifications observed by raman spectroscopy and TEM fully support the conclusions from previous studies of a progressive evaporation of tightly bound water and collagen denaturation [2,910,18,54]. In addition, our Raman, TEM and SAXS analysis also indicate a continuous, non-monotonic mineral nanoparticle growth.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The modifications observed by raman spectroscopy and TEM fully support the conclusions from previous studies of a progressive evaporation of tightly bound water and collagen denaturation [2,910,18,54]. In addition, our Raman, TEM and SAXS analysis also indicate a continuous, non-monotonic mineral nanoparticle growth.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, the observation of all bands at temperatures < 210°C and the relative stability of the I(ν 1 PO 4 )/I(νCH) ratio between 150–210°C strongly suggest that the collagen is not fully denatured in this range. However, the absence of measurable Raman spectra at 250°C as a consequence of an increased background tends to indicate that the full denaturation and even degradation occurs in our samples between 210–250°C, as previously reported by thermal analysis [17] X-ray diffraction [52] and FTIR [18]. …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…When burned, bone undergoes drastic changes structurally as well as within its organic and inorganic matrix, changes which are significantly influenced by the presence or absence of soft tissue . Albeit there is a shift in the atomic percentage of present elements coinciding with the decomposition stage between 300°C and 500°C, this study has demonstrated that the changes in temperature do not affect the gross elemental content of bone, nor was there any significant difference attributable to the factor of soft tissue presence.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been proved useful in fields such as biological anthropology, archaeology, engineering and medicine (Shahack‐Gross, Bar‐Yosef, & Weiner, ; Stiner et al, ; Nakano, Tokumura, & Umakoshi, ; Schiegl, Goldberg, Pfretzschner, & Conard, ; Mkukuma et al, ; Wopenka & Pasteris, ; Wang, Zuo, Huang, Hou, & Li, ; Squires, Thompson, Islam, & Chamberlain, ; Thompson, Islam, Piduru, & Marcel, ; Hollund, Ariese, Fernandes, Jans, & Kars, ; Thompson, Islam, & Bonniere, ; Piga et al, 2016b). Among other things, vibrational spectroscopy has been used (i) to assess bone quality and preservation prior to other advanced analyses such as those based on isotopes (Weiner & Bar‐Yosef, ; Stiner et al, ; Surovell & Stiner, ; Lebon et al, ; Hollund et al, ; Beasley, Bartelink, Taylor, & Miller, ; Dal Sasso et al, ; Lebon, Reiche, Gallet, Bellot‐Gurlet, & Zazzo, ); (ii) to detect biased intra‐ and intersite skeletal compositions as a function of differential preservation environments (Stiner et al, ; Surovell & Stiner, ; Beasley et al, ); (iii) to determine if bone is burned or not and to which intensity (Piga, Malgosa, Thompson, & Enzo, ; Piga, Thompson, Malgosa, & Enzo, 2009; Ellingham, Thompson, Islam, & Taylor, ; Ellingham, Thompson, & Islam, ); (iv) to discriminate between burned bones and bones stained by other taphonomic agents such as manganese oxide (Shahack‐Gross et al, ; Arroyo et al, ); and (v) to potentially discriminate between recent and archaeological materials, as recently reported by Snoeck, Lee‐Thorp, and Schulting (). Several indices have been used for these purposes, especially the crystallinity index (CI), which is sometimes referred to as infrared splitting factor (IRSF) (Stiner et al, ), but also the carbonate to phosphate ratio (C/P); the ratios that quantify the relative amount of A‐ and B‐type carbonates on apatite—API and BPI, respectively; the total carbonate to carbonate B ratio (C/C); the hydroxyl to phosphate ratio (OH/P) (e.g., Stiner et al, ; Thompson et al, ; Snoeck et al, ; and the cyanamide to phosphate ratio (CN/P) (Snoeck et al, ).…”
Section: Introductionmentioning
confidence: 99%